2012
DOI: 10.1136/bmjqs-2012-001134
|View full text |Cite
|
Sign up to set email alerts
|

Use of in situ simulation and human factors engineering to assess and improve emergency department clinical systems for timely telemetry-based detection of life-threatening arrhythmias

Abstract: Background and objectives Medical simulation and human factors engineering (HFE) may help investigate and improve clinical telemetry systems. Investigators sought to (1) determine the baseline performance characteristics of an Emergency Department (ED) telemetry system implementation at detecting simulated arrhythmias and (2) improve system performance through HFE-based intervention. Methods The prospective study was conducted in a regional referral ED over three 2-week periods from 2010 to 2012. Subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…Twenty studies were controlled studies [2527,29,32,34,3644,46,48,49,51,52], two of which were RCTs [44, 51]. The other eight studies were before/after surveys, without a control group [28, 30, 31, 33, 35, 45, 47, 50]. The target populations were staff working in hospitals and nursing homes, including nurses [35, 3739, 4143, 45, 4749, 51], surgeons (3 studies) [27, 44, 46], medical students (4 studies) [25,32,36,52] and other health care workers (8 studies) [26, 2830, 3334, 40, 50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies were controlled studies [2527,29,32,34,3644,46,48,49,51,52], two of which were RCTs [44, 51]. The other eight studies were before/after surveys, without a control group [28, 30, 31, 33, 35, 45, 47, 50]. The target populations were staff working in hospitals and nursing homes, including nurses [35, 3739, 4143, 45, 4749, 51], surgeons (3 studies) [27, 44, 46], medical students (4 studies) [25,32,36,52] and other health care workers (8 studies) [26, 2830, 3334, 40, 50].…”
Section: Resultsmentioning
confidence: 99%
“…The target populations were staff working in hospitals and nursing homes, including nurses [35, 3739, 4143, 45, 4749, 51], surgeons (3 studies) [27, 44, 46], medical students (4 studies) [25,32,36,52] and other health care workers (8 studies) [26, 2830, 3334, 40, 50]. Seventeen studies reported their funding resources [26, 2831, 3337, 43, 4549, 52] and eleven were supported by public funding [2628, 3235,41,4344,46]. Nine studies did not report funding source [27, 32, 3840, 42,4445,51].…”
Section: Resultsmentioning
confidence: 99%
“…10,11 The Food and Drug Administration (FDA) has developed HF guidelines to assist with the design and development of medical devices. 12 Kobayashi et al 13 studied the addition of an automatic external defibrillator (AED) to standard defibrillator-based response systems using simulated in situ cases.…”
Section: Hf In Medicinementioning
confidence: 99%
“…47 Patient telemetry monitoring, a complex clinical process, exemplifies an active area of HF-based research, with a focus on alarm fatigue 48 and the timely detection of life-threatening arrhythmias. 11 There is growing interest in understanding how ED clinicians interact with their work environment through ergonomic and safety analyses of the ED [49][50][51] and through the study of health information technology systems such as patient tracking boards 52,53 and electronic health records. 54 HF has been used in device design within the ED to create a work surface to replace the Mayo stand.…”
Section: Hf In Emmentioning
confidence: 99%
“…In this issue, Kobayashi and colleagues25 describe an intervention to do just that. They demonstrate improvements in performance with an existing technology by reconfiguration based on human factors engineering principles.…”
mentioning
confidence: 99%